PERAN PEMERINTAH NEGERI DALAM PELAYANAN ADMINISTRASI DI NEGERI HITUMESSING KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Rika Juita Gea; Pieter. S. Soselisa; H. V. R. Pattimukay (Universitas Veteran Bangun Nusantara, 2022)
This research is a qualitative descriptive study that aims to identify and analyze the Role of the State Government in Administrative Services in Hitumessing District, Leihitu District, Central Maluku Regency. This research was conducted in Hitumessing Country. With data collection techniques used in the form of observation, interviews, and documentation with a number of informants who are considered to be directly involved in the Role of the State Government in Administrative Services in Negeri Hitumessing, Leihitu District, Central Maluku Regency. The results of this study indicate that the role of the State Government in Administrative Services in Hitumessing District, Leihitu District, Central Maluku Regency has not been optimal or has not been implemented properly. This can be seen from the results of research on service standards, which have several indicators, namely: service procedures, turnaround time, facilities and infrastructure, and competence of service providers. This study concluded that it is necessary to increase the discipline, knowledge and expertise of officers so that the service process can be carried out properly.